Inovasi Pemerintah Daerah dalam Sistem Perencanaan Berbasis Teknologi Informasi (SIMPERDA) untuk mewujudkan Good Governance di Kota Semarang - Reitania Dwi Novia Nainggolan; Teguh Yuwono (Journal of Politic and Government Studies, 2019)
The Innovation Of The Local Government On Technology And Information BasedPlanning Systems In Reaching The Good Governance in Semarang CityReitania Dwi Novia Nainggolanreitanianainggolan02@gmail.comDr.Drs Teguh Yuwono M.Pol.Admintyuwonos22@gmail.comDepartement of Politics and Government Science of FISIP UNDIP SemarangABSTRACTThe innovations of local governments are really important in implementing good andreliable managing systems for a government (Good Governance), in this case the innovationsrelating to the technology based plans by a local government. One of the local governmentsthat has innovations to create managing systems for a good government is the government ofSemarang city. This technology and information based plan for the local developments isdefined as the SIMPERDA programs (SistemPerencanaan Daerah/the Local PlanningSystems).The research method used in this research is the qualitatively descriptive methodusing interviews and documentations as the techniques in obtaining the data. The dataobtained, then, are analyzed using triangulating methods, theories and datum resources.The results of the research are first relating to the adoptions of technologies andinformation used in this SIMPERDA in which using cyber government systems or EGovernmentusing the G to E (Government to Employees) concept, whereas the processes ofplanning systems using SIMPERDA in Semarang city according to schedules/timelines forthe locally developing plans based on Permendagri No. 56 tahun 2017. The differences as theresults of the plans on developments before and after using SIMPERDA in Semarang city arethe guarantees in the availabilities of planning data in developments that can be consideredas a fundamental in making planning considerations for the next year, the accessibilities ofthe online based planning processes, the minimizing of planning processes that areoverlapped, the increases in allocations for MUSRENBANG facilities and thesynchronizations between the results of the suggestions for plans in developments and theRPJMD documents of Semarang city.Key words: Innovation, Local Planning, Good Governance, E-Government